AL-QAWAID AL-SITTAH DALAM RASM AL-MUSHAF (Six Rules of Rasm and the Uniqueness in Qur'an) - Ibnu Rawandhy N. Hula; Amrah Kasim (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2021)
This study examines the six rules and their uniqueness in the writing of the Qur'an, which consists of the following rules: 1) al-Hazf, 2) al-Ziyadah, 3) al-Ibdal, 4) al-Hamazat, 5) al-Wasl and al-Fasl, dan 6) Fihi Qira’atani wa Kutiba ‘ala Ihdahuma. The method used is library research, through descriptive analysis techniques, by identifying, classifying, tabulating, analyzing, and describing. The results showed that 1) al-Qawaid al-Sittah has six basic principles in the science of writing and copying letters, words, and their diacritical marks in manuscripts. These six rules have various passages in some of their orthography; namely: a) alif, ya, waw, lam, nun, on al-hazf, b) alif, ya and waw on al-ziyadah, c) alif derive from ya, alif derive from waw and alif whose origin is unknown on rules al-ibdal, d) according to the rule of al-wasl and fasl, each of them has 17 agreed on words, they are disputed and even excluded, e) in the hamazat rule, the location of a letter affects the form of writing, such as hamzah at the beginning, in the middle, at the end of the word f) Rasm is also influenced by qira'at and can choose one of them in writing it. 2) The differences in writing are dominated by reasons, references, and writing patterns which generally refer to the madhzab with their respective references, namely: 1) Al-Dani with the book al-muqni and 2) Abu Dawud with the book al-tabyin, or madhzab other than the two. 3) In the aspect of exception (mustasnayat) and its uniqueness, it can be seen in the aspect of al-Iqtisar, whose writing patterns are diverse and cannot be equated.